Cambridge O level islamiyat (textbook for paper2) - Nishat, ibn hammad (Cambridge University Press; Karachi, 2019)
Cambridge O Level Islamiyat (Textbook for Paper 2) provides a comprehensive guide to Islamic history, teachings, and practices, specifically designed to support students preparing for their O Level examinations.